Structural characteristic analysis of new type bend-twist coupling blades of large wind turbine - WANG HaiSheng; MIAO WeiPao; LI Chun; ZHANG Li; ZHU HaiBo (Jixie qiangdu)
In order to study the structural performance of the new bend-twist coupling blade, NREL 5 MW blade was taken as the prototype, and the geometric model of the blade was established by using NX Open Grip parameterization language. The composite lamination design was carried out in accordance with the real processing technology, and the aerodynamic force of the blade was obtained by the computational fluid dynamics (CFD) method. The bend-twist coupling characteristics, harmonic response and strength of conventional and bending-torsional coupling blades were analyzed respectively. The results show that the blade tip displacement increases with the increase of the web deflection. For the same angle, the blade tip displacement of γ > 0 blades was smaller than that γ < 0 blades. The bend-twist coupling effect is the most obvious when γ = 10° and 15°. Compared with the conventional blade, the second-order displacement responses of bend-twist coupling blades are significantly reduced. The γ = 15° blade can reduce the stress on the surface and has a good load reduction performance.